Copper(II) and zinc(II) chemistry of a new hexadentate cyclam-based bis-di-2-pyridylmethanamine ligand - Comba, Peter; Linti, Gerald W.; Zajaczkowski-Fischer, Marta; Zessin, Thomas (Journal of inclusion phenomena and macrocyclic chemistry, 2011)
In the endo-conformation of the substituted cyclam derivative L, with two trans-disposed di-2-pyridylmethanamine (dipa) coordination sites (endo: both dipa subunits on the same face of cyclam), the bis-dipa-substituted cyclam platform may form hexacoordinate mononuclear complexes with the two dipa subunits coordinated to one metal ion or dinuclear complexes, when the two dipa subunits are coordinated to two metal ions (oligonuclear linear chain complexes with exo-configured ligands L and metal ions coordinated to the cyclam unit have not been observed so far). Here, the structures, relative stabilities and spectroscopic properties of the mononuclear complexes of CuII and ZnII, which are formed in preference to other structural possibilities, are discussed, and the preference for their formation is also evaluated.
Im Titel ist die 2 bei Copper und zinc als römische Zahl dargestellt
Gesehen am 07.04.2022